2020
DOI: 10.1111/jocn.15563
|View full text |Cite
|
Sign up to set email alerts
|

Understandings of and experiences with evidence‐based practice in practice among nurses in a surgical department: A constructivist approach

Abstract: Aim and objectives To explore nurses’ constructions of the concept of evidence‐based practice through their understandings of and experiences with evidence‐based practice in a clinical care setting. Background The primary purpose of evidence‐based practice is high‐quality patient outcomes. However, the adoption of evidence‐based practice is described as a complex process, and research shows that evidence‐based practice is not translated into practice. Research often explores facilitators and barriers of implem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…23,[26][27][28] Nurse-led research and EBP projects have demonstrated benefits in clinical settings, [29][30][31] yet only an estimated 25% of clinical decisions are made based on evidence, and an even lower percentage results in major changes within the nursing profession. [32][33][34][35] These low implementation rates indicate that the challenges in translating research findings and evidence into practice include issues beyond those of individual knowledge and skill development. Although it may be argued that widespread, rapid-cycle changes occurred during the COVID-19 pandemic (eg, procedures, staffing models, resource allocation), many resulted from necessity rather than enduring paradigm shifts.…”
Section: Implementing Evidence Informed Practice Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…23,[26][27][28] Nurse-led research and EBP projects have demonstrated benefits in clinical settings, [29][30][31] yet only an estimated 25% of clinical decisions are made based on evidence, and an even lower percentage results in major changes within the nursing profession. [32][33][34][35] These low implementation rates indicate that the challenges in translating research findings and evidence into practice include issues beyond those of individual knowledge and skill development. Although it may be argued that widespread, rapid-cycle changes occurred during the COVID-19 pandemic (eg, procedures, staffing models, resource allocation), many resulted from necessity rather than enduring paradigm shifts.…”
Section: Implementing Evidence Informed Practice Changesmentioning
confidence: 99%
“…Although there is much research on the abilities of individual nurses in regard to EBP, the importance of the context in which interventions are to occur cannot be overstated 23,26-28 . Nurse-led research and EBP projects have demonstrated benefits in clinical settings, 29-31 yet only an estimated 25% of clinical decisions are made based on evidence, and an even lower percentage results in major changes within the nursing profession 32-35 . These low implementation rates indicate that the challenges in translating research findings and evidence into practice include issues beyond those of individual knowledge and skill development.…”
mentioning
confidence: 99%
“…The educational level attainment of acute care nurses from Turkey was positively associated with awareness of procedures and knowledge of evidence‐based wound care 20 . Nevertheless, nurses' theoretical knowledge of EBC does not habitually translate into providing EBC 30,34 . An Australian study reported that most acute care nurses (75.4%) sought the advice of wound specialists in contrast to clinical guidelines (60.7%) for information on EBC 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the introduction of standardised surgical site management guidelines, 29 acute care nurses' rely on practice‐based experience, challenging consistent, EBC delivery. 30 , 31 , 32 , 33 The educational level attainment of acute care nurses from Turkey was positively associated with awareness of procedures and knowledge of evidence‐based wound care. 20 Nevertheless, nurses' theoretical knowledge of EBC does not habitually translate into providing EBC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation